2008
DOI: 10.5539/mas.v2n4p131
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Perspective and Pollution Indicator in Mengkabong Mangrove Sediment Sabah

Abstract: The role of tidal processes on intertidal surface sediments is frequently stated but rarely investigated due to the methodological restrictions. This study provides a basis for describing the tidal effects on the mangrove sediment. It reports investigations into the chemical composition of mangrove surface sediment in Mengkabong lagoon, Sabah, Malaysia. The levels of 16 parameters were determined in 33 surface sediment samples at high and low tides. The studied parameters showed high values at high tide compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Soil physico chemical parameters were conducted to determine the influences of each OTUs with reference to soil type preference. It was generally observed that depth 1-87m (zone of monotypic occurrence of OTU 1 was 1-83m) was Conductivity as a measure of the degree of salinity, showed an increase in the salinity of mangrove water relative to that of seawater, confirming the ability of mangrove to tolerate high salt levels [34]. The trend of increasing salinity content from the high intertidal zones occupied by OTU 1 and to some extent, OTU 2 to mid-stream occupied by OTU 2 and 3 to the low intertidal zone or terrestrial border occupied by OTUs 4 and 5.…”
mentioning
confidence: 89%
“…Soil physico chemical parameters were conducted to determine the influences of each OTUs with reference to soil type preference. It was generally observed that depth 1-87m (zone of monotypic occurrence of OTU 1 was 1-83m) was Conductivity as a measure of the degree of salinity, showed an increase in the salinity of mangrove water relative to that of seawater, confirming the ability of mangrove to tolerate high salt levels [34]. The trend of increasing salinity content from the high intertidal zones occupied by OTU 1 and to some extent, OTU 2 to mid-stream occupied by OTU 2 and 3 to the low intertidal zone or terrestrial border occupied by OTUs 4 and 5.…”
mentioning
confidence: 89%